Ancient calendars and constellations - Plunket, Emmeline M. (Emmeline Mary), 1835- (Salt Lake City, UT : Project Gutenberg, 2023)
"Ancient Calendars and Constellations" by Emmeline M. Plunket is a historical account written in the early 20th century. The book explores the development of ancient calendars and their connection to constellations, particularly focusing on methodologies and observations made by ancient civilizations like the Babylonians and Assyrians. The central theme revolves around how these early systems of timekeeping are interwoven with astronomical knowledge and mythology. At the start of the book, the author provides a preface that outlines her intentions and the academic discussions that led to the assembled papers. These papers reference early astronomical research and argue for the significance of the Accadian calendar, suggesting that it may date back to around 6000 B.C. The opening portion elaborates on the complexities of ancient timekeeping and loss of seasonal alignment, presenting insights into how the various ancient cultures' calendars reflected their observations of celestial events and constellations. Plunket stresses the importance of this knowledge and how a deeper understanding of calendars can unveil connections with historical narratives and mythologies across civilizations. (This is an automatically generated summary.)
The Accadian calendar -- The constellation Aries -- Gu, eleventh constellation of the Zodiac -- The Median calendar and the constellation Taurus -- Astronomy in the Rig Veda -- Notes: Ahura Mazda, etc. -- Ancient Indian astronomy -- The Chinese calendar, with some remarks with reference to that of the Chaldeans.
Release date is 2023-02-16
MFR, Harry Lamé and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Constellations; Astronomy, Ancient; Calendar